IMPROVING MANAGERIAL COMPETENCE OF PEAT ARBORETUM MANAGERS POST THE COVID-19 PANDEMIC IN BENGKALIS DISTRICT - Zulkarnaini, Zulkarnaini; Sadad, Abdul; Bedasari, Hafzana; Nasution, Mimin Sundari; Meiwanda, Geovani (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The existence of the Peat Arboretum is very important for environmental preservation, especially in areas that have extensive peatlands. It's just that its existence is less of a concern to the parties concerned. The manager has experienced a lack of income due to the absence of adequate management activities. The purpose of this community service activity is to improve the managerial competency of managing the Post-Covid 19 Pandemic Peat Arboretum in Bengkalis Regency. The implementation method used is a participatory approach and counseling and active assistance aimed at the management of the Peat Arboretum in Bukit Batu District, Bengkalis Regency. The results of the dedication show that the management of the Peat Arboretum as eco-tourism requires support from various parties. It is not enough just to rely on corporate CSR or government projects. Especially since the Covid 19 pandemic practically the activity of visiting tourists to locations has been greatly reduced. Managerial competence is felt to be important to the attention of all stakeholders in the management of the Peat Arboretum, because all team members can experience an increase in their leadership competence. Managerial competence makes coordination and communication easier, members are more open, and members feel valued and there is member attachment to the team.